ANALISIS MINAT WISATA ROHANI DI CANDI HATI KUDUS GANJURAN - Krestanto, Hery (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2015)
The purpose of this study was to determine the interest in spiritual tourism in tyas palace temple sacred heart Ganjuran, the research was conducted in the temple sacred heart Ganjuran tyas palace. Tyas temple sacred heart Ganjuran Ganjuran located in Bantul district of Yogyakarta as a special propinsidaerah Dutch heritage, inculturation Hindu temple has a Buddhist, Javanese, Europe, inculturation Hindu temple and a Buddhist look of relief created, while the Java ikulturasi visible from carnival procession Perwita cider, ikulturasi europe seen from the cross of the existing The technique of collecting data using interviews and observations, research results show an interest in spiritual travel temple palace Ganjuran tyas there who believe that the essence Perwita water can cure various diseases, find a mate and other petition, people who come to the temple tyas palace is not only a religious Ganjuran Catholic but of various religions such as Islam, Hinduism, Buddhism, they come like getting wangsi the purpose Keyword : Minat, Wisata Rohani, Candi Hati kudus.